2015
DOI: 10.1016/j.sbspro.2015.06.338
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Comparison of Participation and Conventional Banking Sectors in Turkey between 2007-2013

Abstract: The reason of paying attention to the relative efficiency of banks will differ in conjunction with the perspectives of related parties such as regulators, customers, managers, and stakeholders. Within this context, banking is an over regulated sector by governments. It means that banks operate their functions in compliance with these frameworks. Banking sector is also enormously sensitive against economic changes that lead to the fragile side of the economy. Hence, from the regulators' perspective, inefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Output orientation attempts to maximize outputs without increasing inputs. Input orientation is preferred in banking analyses because banks usually have no direct control over the amount of services demanded by their clients, however they can control inputs [Yilmaz, Güneş 2015].…”
Section: Theoretical Background -Measuring Bank Efficiencymentioning
confidence: 99%
“…Output orientation attempts to maximize outputs without increasing inputs. Input orientation is preferred in banking analyses because banks usually have no direct control over the amount of services demanded by their clients, however they can control inputs [Yilmaz, Güneş 2015].…”
Section: Theoretical Background -Measuring Bank Efficiencymentioning
confidence: 99%
“…The results also showed that banks with a large size are more efficient than small sized banks and banks with many branches numbering more efficient than the bank with fewer branch. Research Islamic banks have also been much done 7 to calculate the relative efficiency based on the perspective of regulators, consumers, managers, and stakeholders. Results showed that the banking sector is sensitive to economic changes.…”
Section: Efficiency Approach At Banksmentioning
confidence: 99%
“…Total deposits and capital were used as the input variables. Total loan, income and investments were used as the output variables in the study (Yılmaz and Güneş, 2015). Technical efficiencies of commercial banks in Turkey were measured with data envelopment analysis (Ulaş and Keskin, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%